Between the Past and Present: Effective Ways of Teaching English in Iraqi High Schools (Journal of the College of Basic Education, 2022)
The failure of Iraqi high school graduates in using English communicatively is the main focus of educators and curriculum designers. Teachers’ preparation to teach language and methods of teaching used might be one of the reasons for this failure. This study investigates the difference between teaching English according to the traditional way before 2003 and the modern way of teaching adopted after that. Interviews were conducted with four Iraqi high school graduates, two of which graduated before 2003 whereas the other two represented the modern changes applied on both the curriculum and methods of teaching English after 2003. The results of the study showed that those changes were not suitable for the unique English education environment in Iraq which deals with English as a foreign language.Keywords: English as a Foreign Language (EFL), First Language (L1), Grammar Translation Method (GTM), Communicative Language Teaching (CLT)